2017
DOI: 10.1177/2050312117743673
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and falls: Applying Beers criteria to medication review in Parkinson’s disease

Abstract: Objectives:Our goal was to assess the association between potentially inappropriate medication use and risk of falls in the Parkinson’s disease population.Methods:This was a retrospective cohort study conducted at an outpatient Parkinson’s Disease Treatment Center. Individuals 65 years of age or older, diagnosed with Parkinson’s disease who attended at least three visits in 2015 for physical, occupational therapy, or physician’s visits were included in the study. Electronic medical records were utilized to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 15 Another study in the United States associated falls among a Parkinson’s disease population with the PIMs that are recommended to be avoided in patients with a history of falls in the 2015 AGS-Beers Criteria. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 15 Another study in the United States associated falls among a Parkinson’s disease population with the PIMs that are recommended to be avoided in patients with a history of falls in the 2015 AGS-Beers Criteria. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the prescription of benzodiazepines in dementia and ibuprofen in gastric ulceration participants 20 . Another study reported about the use of PIMs in Parkinson’s disease 27 . In our study, no one was prescribed any of the drugs that should be avoided in the disease condition he/she was suffering from.…”
Section: Discussionmentioning
confidence: 53%
“…20 Another study reported about the use of PIMs in Parkinson's disease. 27 In our study, no one was prescribed any of the drugs that should be avoided in the disease condition he/she was suffering from.…”
Section: Ta B L E 3 Distribution Of Adrs Based On Ctcae Grading and C...mentioning
confidence: 78%
“…The changes in gait worsen and motor fluctuations, dyskinesias, and freezing of gait become frequent and are accompanied by reduced balance and postural control, all of these exposing the patient to a severe risk of falling. More than that, the decline in the motor capacity can lead, in advanced stages, to the need of wheelchair use [75][76][77]. We expect to see these changes in the correlation coefficient matrix to facilitate gait pattern interpretation.…”
Section: Discussionmentioning
confidence: 99%